Pengaruh Earning Per Share Terhadap Harga Saham Dengan Debt Ratio Sebagai Variabel Pemoderating Pada PT. Akasha Wira Internasional Tbk - Siti Nurjanah, Dara; Munawar, Andri Helmi; Hadiani, Dian; Suherni, Neni (Jurnal Keuangan dan Bisnis, 2023)
This study aims to determine and analyze earnings per share, stock price and debt ratio, and the value influence of earnings per share on stock prices with debt ratio as a moderating variable at PT Akasha Wira Internasional Tbk from 2009 to 2018. The study applied a quantitative approach in terms of explanatory method. It used secondary data with purposive sampling techniques. The statistical method used is Moderated Regression Analysis. The influence value of earnings per share on the stock prices is 35.30%. The result of the hypothesis test reveal that earning per share does not have any significant effect on the share prices of PT Akasha Wira International Tbk. Likewise, the existence of the debt ratio as a moderating variable does not provide any significant influence either. In other words, the debt ratio does not change or determine the influence value of earning per share on stock prices. At last, the correlation relationship has a negative direction which means that if the interaction of earnings per share and debt ratio increases, the stock prices will fall.